PENDIDIKAN AKHLAK DALAM PERSPEKTIF HAMKA (Studi Q.S. Luqman dalam Tafsir Al-Azhar) - Abdullah Sani Ritonga, 1, Achyar Zein, Syamsu Nahar (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstract: Islamic education is education that originates from the Koran. Interpretation is a description ofscholars regarding the content and value of the Qur’an. Based on these two things, this study aims to issueelements regarding moral education based on Hamka’s description in the book entitledTafsir Al-Azhar.The elements in question are understanding of moral education, its purpose, method of implementation,moral resources, moral education material, and moral education components. Through library researchandthe maudhû’i method initiated by Shaykh Mahmud Syaltut, it was found that the definition of moraleducation according to Hamka is education that directs human morals to the true aqeedah, the rightattitude, the right way of caring, always doing the right thing, and being civilized and correct manners. Thepurpose of moral education is to direct the behavior of students to those in understanding. The method ofimplementation is lectures, demonstrations, and examples. Moral sources are from Allah, the guide of theMessenger of Allah, and the attitude of the community around the students. Moral education material is notshirk, prayer, patience, follow the procedure, respect for parents if parents call on the truth, associateparents properly if people call on polytheism, amar ma’ruf nahi mungkar, do not look away when talking,do not be arrogant in behave, don’t be proud of yourself in life, simple in walking and soft in speakingaccording to the context. The moral education component consists of educators, students and educationevaluation. In this study also described the relevance of moral education in Hamka’s perspective oneducation today, especially character education. It was found that there was a real relevance betweenmoral education and character education. The relevance is in the sense and purpose of producing goodlearners, with good definitions that differ between the two: good according to moral education is good inreligious review, while good according to character education is good in the review of Pancasila as theprinciple of the state. Likewise in other elements. With this relevance, it was concluded that there wasactually no conflict between the two but rather moral education complemented things that had not beenformulated by character education.Keywords: Tafsir Al-Azhar, Hamka, Moral Education, Character Building Education